Aplikasi Zeolit+KMnO4 dan Silika Gel Untuk Memperpanjang Masa Simpan Cabai Rawit Merah (Capsicum frutescens L.) - Rike Nurmala; Emmy Darmawati; Setyadjit Setyadjit (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2024)
Cayenne pepper is a fruit vegetable commodity with a climacteric type of respiration pattern that produces ethylene. This research aims to maintain and extend the shelf life of red cayenne pepper by applying an ethylene adsorber bag (EAB). The material used in this research is red cayenne pepper (Capsicum frutescens L.) variety ori 212. The research stage is divided into two parts: preliminary research and main research. Measuring the production of ethylene and H2O in red cayenne pepper following harvesting is done in the preliminary stage. The study's primary goal is to preserve and increase the shelf life of red cayenne pepper by using EAB, storing it at 27 ± 2 °C for 10, 15, and 20 days, and then observing the results once the EAB is removed. If the data is normally distributed, it is analyzed using the t-sample test, and if it is not normally distributed with the Mann-Whitney test. The outcomes showed that using EAB to keep red cayenne pepper fresh for 10 days in scenario 1, 15 days in scenario 2, and 18 days in scenario 3 at room temperature (27±2 °C).